Моделювання якості гарбузово-морквяного напівфабрикату - Коваль, Ольга Андріївна; Сосюк, Аліна Олександрівна (My University, 2018)
Представлено результати дослідження впливу різного співвідношення компонентів із гарбуза та моркви на фізико-хімічний та вітамінний склад і органолептичні показники гідролізованого пюре. Порівняння харчової, енергетичної цінності, вмісту харчових волокон, вітамінного, мінерального складу проводили за співвідношення площ пелюсткових колових діаграм відповідних складових. Якісну оцінку дрібнодисперсних систем у вигляді пюре з каротинвмісних овочів (гарбуза, моркви) виконали методом бальної оцінки за органолептичними показниками. Порівняння органолептичних показників якості пюре з гарбуза, моркви та їх сумішей до найкращого варіанту виконували за співвідношенням площ пелюсткових колових діаграм. Аналіз отриманих співвідношень площ пелюсткових колових діаграм для гарбуза, моркви та їх сумішей виявив кращий модельний зразок. Розроблено технологію дрібнодисперсних систем у вигляді пюре з каротинвмісних овочів із застосуванням волого-термічної обробки в пароконвекційній печі. The content of the vitamin and trace element composition, the nutritional and biological value of a two-component pumpkin-carrot mixture, pumpkin and carrots are analyzed analytically. A comparative analysis of organoleptic indicators of quality of fine disperse systems in the form of mashed with carotene-containing vegetables (pumpkin, carrot) using wet-heat treatment and subsequent mechanical decomposition is carried out. Comparison of foodstuffs, power value, maintenance of foodfibres, composition of vitamins and minerals conducted fromthe point of view of correlation of areas of the petalouscircular graphs of corresponding components. Qualityestimation of the micronized systems as a puree from thecarotin of containing vegetables (pumpkins, carrot) wasconducted by the method of count for organoleptic parameters. Comparison of organoleptic descriptionsa puree from a pumpkin, carrot and their mixtures with thebest variant it was executed on correlation of f the petalous circular graphs grounds. The analysis of the got correlationsof areas of the petalous circular graphs showed for apumpkin, carrot and their mixtures, that the best standard incomposition and tasting is mixture vegetable of puree №2, consisting of 50% pumpkin and 50% carrot. The obtained results allowed to develop a technology of fine disperse systems in the form of mashed with carotene-based vegetables using wet-heat treatment in a steam-convection oven.
Keywords: кафедра технології ресторанної і аюрведичної продукції; гарбуз; морква; пюре з гарбуза; пюре з моркви; гідролізоване пюре; гарбузово-морквяний напівфабрикат; якість; pumpkin; carrots; pumpkin puree; carrot puree; mashed potatoes; mashed carrots; hydrolyzed puree; pumpkin and carrot semi-finished product